Plasma Formation during Acoustic Cavitation: Toward a New Paradigm for Sonochemistry. (4th May 2014) - Nikitenko, Sergey I.
Abstract : The most recent spectroscopic studies of single bubble (SBSL) and multibubble (MBSL) sonoluminescence reveal that the origin of extreme intrabubble conditions is related to nonequilibrium plasma formed inside the collapsing bubbles. Analysis of the relative populations of OH(A 2 Σ + ) vibrational states observed during MBSL in water saturated with noble gases shows that in the presence of argon at low ultrasonic frequency weakly excited plasma is formed. At high-frequency ultrasound the plasma inside the collapsing bubbles exhibits Treanor behavior typical for strong vibrational excitation. Plasma formation during SBSL was observed in concentrated H2 SO4 preequilibrated with Ar. The light emission spectra exhibit the lines from excited Ar atoms and ionized oxygenO 2 + . Formation ofO 2 + species is inconsistent with any thermal process. Furthermore, the SBSL spectra in H2 SO4 show emission lines from Xe +, Kr +, and Ar + in full agreement with plasma hypothesis. The photons and the "hot" particles generated by cavitation bubbles enable the excitation of nonvolatile species in solutions increasing their chemical reactivity. Secondary sonochemical products may arise from chemically active species that are formed inside the bubble but then diffuse into the liquid phase and react with solution precursors to form a variety of products.